Incidence and determinants of left ventricular ejection fraction (LVEF) recovery in heart failure with reduced ejection fraction (HFrEF) of non-ischemic aetiology; a hospital-based prospective longitudinal registry study - Sanjeev Kumar; Prakash Chand Negi; Sanjeev Asotra; Jitender Kumar; Rajeev Merwah; Rajesh Sharma; Ritesh Kumar; Vinay Bhardwaj; Preetam Singh Thakur (Indian Heart Journal)
Background: Heart failure with reduced ejection fraction (HFrEF) can show recovery in some patients, especially with non-ischemic causes, leading to better outcomes. Recovery varies due to factors like aetiology and severity of myocardial injury. This study examines the incidence and predictors of left ventricular ejection fraction (LVEF) recovery in non-ischemic HFrEF patients. Methods: This was a prospective observational study conducted at a tertiary care hospital, involving 500 patients with non-ischemic HFrEF (baseline LVEF <40 %). Patients were followed for a duration of 8 years (2011–2023) with periodic clinical assessments and annual echocardiographic evaluations. Data on comorbidities, baseline cardiac function, medication adherence, and clinical events were collected. The incidence rate of LVEF recovery was determined, and Kaplan–Meier survival analysis was used to identify recovery trends over time. Predictors of recovery were evaluated using Cox proportional hazards models. Results: Cumulative incidence of LVEF recovery was 27.4 % (95 % CI: 23.7–31.5) at 8 years, with an incidence rate of 4.5 per 100 person-years. Higher baseline LVEF (≥30 %) strongly predicted recovery (HR: 2.17, p < 0.001), while dilated LV (LVEDD ≥60 mm, HR: 0.6, p = 0.02) and diabetes (HR: 0.36, p = 0.01) were associated with lower recovery. Education (≥Class 5) was linked to better recovery (HR: 1.45, p = 0.04). Beta-blockers showed a potential but nonsignificant benefit. Conclusion: Nearly one-fourth (27.4 %) of patients achieved LVEF recovery over 8 years, with higher baseline LVEF and education associated with better outcomes, while adverse cardiac remodeling and diabetes were linked to lower recovery.